Volumetric full-range magnetomotive optical coherence tomography - Ahmad, Adeel (J Biomed Opt, 2014)
Magnetomotive optical coherence tomography (MM-OCT) can be utilized to spatially localize the presence of magnetic particles within tissues or organs. These magnetic particle-containing regions are detected by using the capability of OCT to measure small-scale displacements induced by the activation of an external electromagnet coil typically driven by a harmonic excitation signal. The constraints imposed by the scanning schemes employed and tissue viscoelastic properties limit the speed at which conventional MM-OCT data can be acquired. Realizing that electromagnet coils can be designed to exert MM force on relatively large tissue volumes (comparable or larger than typical OCT imaging fields of view), we show that an order-of-magnitude improvement in three-dimensional (3-D) MM-OCT imaging speed can be achieved by rapid acquisition of a volumetric scan during the activation of the coil. Furthermore, we show volumetric (3-D) MM-OCT imaging over a large imaging depth range by combining this volumetric scan scheme with full-range OCT. Results with tissue equivalent phantoms and a biological tissue are shown to demonstrate this technique.